2015
DOI: 10.1021/acs.iecr.5b02771
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Reactions of Biomolecules Relevant for Microalgae Liquefaction

Abstract: Hydrothermal liquefaction (HTL) of microalgae, a process that uses water at high temperature and high pressure to make a renewable crude bio-oil, is receiving increased attention. Understanding the governing reaction pathways for the biomolecules in the microalgae cell could lead to improved conversion processes. This review collects information pertinent to the behavior of microalgae biomolecules (e.g., proteins, polysaccharides, lipids, chlorophyll) and their hydrothermal decomposition products (e.g., amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(74 citation statements)
references
References 145 publications
2
72
0
Order By: Relevance
“…The decomposition of amino acids in water has been extensively studied for its applications to organic geochemistry (e.g. Ito et al, 2006Ito et al, , 2009, extracting and recycling proteinaceous products in industry or biotechnology (e.g., Zhu et al, 2011, Changi et al, 2015 and in investigations of the hydrothermal origin of life (e.g. Bada et al, 1995).…”
Section: Rate Constant Calculationsmentioning
confidence: 99%
“…The decomposition of amino acids in water has been extensively studied for its applications to organic geochemistry (e.g. Ito et al, 2006Ito et al, , 2009, extracting and recycling proteinaceous products in industry or biotechnology (e.g., Zhu et al, 2011, Changi et al, 2015 and in investigations of the hydrothermal origin of life (e.g. Bada et al, 1995).…”
Section: Rate Constant Calculationsmentioning
confidence: 99%
“…Most of saturated fatty acids were C 16 compounds which reacted before C 18 compounds (Watanabe , et al, 2006). Hydrolysis of protein in subcritical water are well studied (Changi, et al, 2015). In fact, protein breaks down into amino acids which explains their presence in WSP.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Besides, the pH of the aqueous slurry was reported as a critical factor to amino acid conversion. The acidic condition would prevent the conversion of amino acids like methionine and arginine while favoring the conversion of leucine and serine . Sakata et al reported the enhancement of the oligomerization pathways to form the dimer of glycine under the alkaline environment.…”
Section: Resultsmentioning
confidence: 99%